"OK, Google, why do I use you?" Motivations, post-consumption evaluations, and perceptions of voice AI assistants. (September 2021) - Choi, Tae Rang; Drumwright, Minette E.
Highlights: Five primary motivations for using voice AI assistants are identified. Life efficiency and information motives determine attitudes, behavioral intention. Only social interaction motive determines social attraction and perceived-as-friend. Only life efficiency motive determines perceived-as-assistant. Only information motive determines perceived-as-technology. Abstract: Voice-activated, artificial intelligence–based assistants (voice AI assistants) have become an integral part of everyday life because they can be easily activated to complete numerous tasks. However, little is known about what motivates people to use them or how these motivations influence users' post-consumption evaluations and perceptions. This study develops measures to capture uses and gratifications related to voice AI assistants. It identifies five primary motivations for use—social interaction, personal identity, conformity, life efficiency, and information. Results show that the utilitarian motivations of life efficiency and information influence all post-consumption evaluations and behavioral intentions positively (i.e., users' attitudes, satisfaction, and intentions to continue using voice AI assistants). However, social motivations are also important. Social interaction and conformity motivations also influence user satisfaction, and the conformity motivation shapes individuals' intentions to continue using voice AI assistants. The findings further demonstrate that users' motivations influence perceptions of their voice AI assistants' roles. In keeping with the "Computers Are Social Actors" (CASA) paradigm, users motivated by social interaction are likely to perceive a voice AI assistant as socially attractive and as a friend, whereas users motivated by life efficiency are likely to perceive it as an assistant. Users motivated by information are more likely to perceive a voice AI assistant as technology, while those motivated by social interaction are less likely to do so. The implications of these findings are discussed, and recommendations for future research are provided.